2006
DOI: 10.1038/ncponc0660
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor receptor-β in Gorham's disease

Abstract: SUMMARYBackground-A 17-year-old male presented with pain in his lower-left chest. He had no significant medical history and was previously in good health. He had a fractured ninth left anterior rib and the tenth, eleventh and twelfth ribs were absent, which was thought to be a congenital anomaly. Several months later, he presented again with back pain, an enlarging mass in the lower-left chest wall, erosion of the lateral pedicles of the lower thoracic vertebrae and pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 16 publications
2
68
0
10
Order By: Relevance
“…It is controversial whether osteoclasts are present or not [6]. In some cases, such as in those of Gorham and Stout [3], osteoclasts have not been found in areas of resorption or reparative osteogenesis, and therefore angiomatosis is thought to be responsible for the process [7,8]. Recent studies have suggested that vascular endothelial growth factor is a marker of disease activity [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether osteoclasts are present or not [6]. In some cases, such as in those of Gorham and Stout [3], osteoclasts have not been found in areas of resorption or reparative osteogenesis, and therefore angiomatosis is thought to be responsible for the process [7,8]. Recent studies have suggested that vascular endothelial growth factor is a marker of disease activity [9].…”
Section: Discussionmentioning
confidence: 99%
“…С учетом вариабельности скорости остеолиза наиболее перспективными биомаркерами его активности счита-ются VGEF-A [7,10,37] и интерлей-кин-6 [12,17,18,43], уровень которых при GSD может быть повышен. Вме-сте с тем показатели этих цитокинов могут оставаться и нормальными [25,37], поэтому продолжаются активные поиски других биомаркеров остеоли-за -VEGF-C [37], PDGF-BB [25], sRANKL и остеопротегерина [18].…”
Section: рисunclassified
“…Another important point about the histopathology of Gorham-Stout syndrome was noted by Colucci et al [11] (in 2006), who found that the cells they isolated from a patient's lesion belonged to a monocyte-macrophage lineage and could release high amounts of osteoclastogenic and angiogenic molecules. Additionally, Hagendoorn et al [12] (in 2006) underlined the critical role that could play the signaling pathway of the PDGFR-b (receptor of the lymphangiogenic growth factor Platelet Derived Growth Factor BB) in the pathogenetic mechanism of the disease. Besides, in 2007, Bruch-Gerharz et al [5] tried to shed more light onto the pathogenesis of the syndrome, writing about lymphatic vascular malformations involving the skin and the soft tissues adjacent to the diseased bone.…”
Section: Etiopathologymentioning
confidence: 99%